Crossing boundaries: Social-scientific reading of the faith of a Canaanite woman (Mt 15:21-28) - Kgatle, Mookgo S. (Stellenbosch theological journal, 2018)
Social-scientific criticism refers to an interpretation of the biblical text that takes into cognizance the social system that produced that text. This article presents a social scientific reading of the faith of a Canaanite woman in Matthew 15:21-28. The article outlines models of social systems in Matthew 15:21-28 like landscape and spatiality, gender and sexuality, ethnicity, purity, and social status in order to achieve a social scientific reading. The purpose of this article is to firstly demonstrate that the models of social system in Matthew 15:21-28 served as boundaries to the faith of a Canaanite woman. Secondly, it is to demonstrate that the Canaanite woman crossed such boundaries in Matthew 15:21-28 for her daughter to receive healing. Lastly, the Canaanite woman serves as a model for South African women today who have to cross boundaries like landscape and spatiality, gender and sexuality, ethnicity, purity, and social status.